Ciprofloxacin disrupts testosterone synthesis in mice via downregulating StAR expression through NR4A1 pathway - Lirui Hou; Yuhan Fu; Yue Zhao; Chongshan Dai; Chong Zhao; Lihong Fan; Hongbo Hu; Shutao Yin (Ecotoxicology and Environmental Safety)
Ciprofloxacin (CIP) is a synthetic third-generation quinolone antimicrobial agent with broad-spectrum bactericidal activity and widely used in human and veterinary medicine. Some studies have shown that quinolone antibiotics are endocrine disruptors, but the effect of early-life exposure to CIP on testosterone production remains unclear. Using adolescent male C57BL/6 J mice (n = 6 per group) exposed to CIP (1–75 mg/kg) for 30 days, combined with in vitro models of mouse testicular cells (TM3, TM4, GC-2spd), this study investigated the toxic effects of CIP on testosterone synthesis. Animal studies showed that 1 mg/kg CIP significantly decreased serum testosterone levels and increased LH and FSH levels. With increasing doses of CIP, the sperm count of mice was significantly reduced and accompanied by tissue damage in the testes. Through Western blotting, qPCR, and molecular docking analyses, we identified StAR as the key protein mediating CIP-induced testosterone suppression. CIP was found to affect testosterone synthesis by influencing the expression of testosterone synthesis-related proteins in both in vivo and in vitro. Transcriptomic sequencing of pituitary tissues revealed dose-dependent alterations in genes related to GnRH secretion and cAMP signaling pathways. For the first time, we confirmed that CIP inhibits the transcription of StAR by downregulating NR4A1 expression, ultimately blocking testosterone synthesis. In TM3, TM4, and GC-2spd cells, all three cellular activities were inhibited with increasing concentrations of CIP, which causes S-phase cycle block in TM3 and G2/M-phase cycle block in TM4. The study demonstrates that CIP inhibits testosterone synthesis via the NR4A1/StAR pathway, suggesting CIP is an endocrine disruptor and implying low-dose CIP exposures cause more severe effects that should be of widespread concern.